The industrial storage tank transformed into architecture and the landscape: A new look through Land Art - Cabrera Vergara, María (Estoa. Journal of the Faculty of Architecture and Urbanism, 2017)
The appearance of colossal industrial deposits in our rural and urban landscapes entailed, to say the least, much criticism and a strong sentiment of rejection. And once obsolete and abandoned, their presence continued to provoke equal or even greater skepticism. This study aims to value how the intervention in these objects and their transformation into architecture has modified their relationship with their surrounding environment as well as the current perception people have from them, and to demonstrate the potential they hold from the landscaping point of view. The analysis of some of these projects evidence on the one hand, that due to the unique nature of these artifacts, the architects who had to face the task of transforming them had to reinvent their way of working, adopting methodologies, strategies and tools from the artistic discipline; and on the other, that the conceptual potential of these artifacts cannot be fully understood without taking into account this artistic and landscaping dimension. Keywords: art, industrial, land art, landscape, storage tank.